2021
DOI: 10.1101/2021.09.09.459426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trans-cellular tunnels induced by the fungal pathogen Candida albicans facilitate invasion through successive epithelial cells without host damage

Abstract: The opportunistic fungal pathogen Candida albicans is normally commensal, residing in the mucosa of most healthy individuals. In susceptible hosts, its filamentous hyphal form can invade epithelial layers leading to superficial or severe systemic infection. Invasion is mainly intracellular, though it causes no apparent damage to host cells. We investigated the invasive lifestyle of Candida albicansin vitro using live-cell imaging and the damage-sensitive reporter galectin-3. Quantitative single cell analysis s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
(129 reference statements)
1
0
0
Order By: Relevance
“…We found that the host implements robust responses to offset the stresses C. albicans creates on the epithelial PM during invasion. By electron microscopy, the invasion pocket was reported recently to have inflated membranes with numerous associated vesicles ( Lechat, 2021 ), reminiscent of the blebs we document. Our cell-based studies are also in accordance with in vivo mouse and zebrafish candidiasis models that link ECE1 expression with C. albicans pathogenicity and invasiveness ( Moyes et al., 2010 ; Swidergall et al., 2019 ).…”
Section: Discussionsupporting
confidence: 58%
“…We found that the host implements robust responses to offset the stresses C. albicans creates on the epithelial PM during invasion. By electron microscopy, the invasion pocket was reported recently to have inflated membranes with numerous associated vesicles ( Lechat, 2021 ), reminiscent of the blebs we document. Our cell-based studies are also in accordance with in vivo mouse and zebrafish candidiasis models that link ECE1 expression with C. albicans pathogenicity and invasiveness ( Moyes et al., 2010 ; Swidergall et al., 2019 ).…”
Section: Discussionsupporting
confidence: 58%